Profil Kemanusiaan dalam Antologi Kumpulan Cerpen Pilihan Kompas Tahun 2010 - Maryunita, Roza; Tamsin, Andria Catri; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2012)
This research is purposed to describe humanity profile that presented in Kompas’s short-stories selection, from eight pint of view, which are: (1) human aspect and affection, (2) human aspect and embellishment, (3) human aspect and suffering, (4) human aspect and justice, (5) human aspect and responsibility, (6) human aspect and way of life, (7) human aspect and discomfort, and (8) human aspect and expectation. Data sources in this research are ten short-stories that contain in 2010 Kompas’s short-stories selection anthology. Data gathered in four steps: (1) read and conceive anthology of 2010 Kompas’s short-stories selection, (2) remark any humanity profile that existed in 2010 Kompas’s short-story selection anthology, (3) inventorying data, and (4) clarifying data. The result in this research reveal eight aspect of humanity profiles from ten short-stories in 2010 Kompas’s short-story selection anthology. But these profiles isn’t contain in every short-stories.